Envelhecimento ativo na concepção de um grupo de enfermeiros - Bidel, Regina Maria Rockenbach (2015)
Aging is a process that reaches members of the public, whether by physical, biological, psychological, social, among others. Knowledge about the multidimensionality of human aging is necessary to all professionals working in the context of primary care, especially nurses. The role of this professional, through nursing consultation, either in the basic health unit is at home or through health education, individually or in groups, presents guiding practices for nurses performance in the art of care, since in primary care, the approach of human aging and the elderly, it is increasingly necessary. The study aimed to identify the concepts that a group of nurses is about active aging. Exploratory and descriptive research with qualitative approach, using the focal method, developed in a municipality located in northern Rio Grande do Sul, in the Alto Uruguay region. Participants were eight nurses who met the inclusion criteria: being a nurse and be working in primary care for at least one year, regardless of the work performed. The results were compiled in a scientific, annexed to the study entitled "Active aging in the design of a group of nurses working in primary care." The study identified that nurses comprise the active aging in a stereotypical way, giving the interpretation to active, those age satisfactorily in physical, psychological and social dimensions. Aging is understood as not active for those who age in unfavorable conditions in the listed dimensions. Thus, it is vital to have training courses for nurses, especially for those who work in primary care. This strategy will allow moments of reflection and expansion of knowledge about gerontological issues, so they can act in full, in the process of living and aging, meeting the needs both of the elderly, as the family and even society in general